2019
DOI: 10.1111/jcmm.14271
|View full text |Cite
|
Sign up to set email alerts
|

rSJYB1 inhibits collagen type I protein expression in hepatic stellate cells via down‐regulating activity of collagen α1 (I) promoter

Abstract: YB1 is a negative regulator in liver fibrosis. We wondered whether SJYB1, a homologous protein of YB1 from Schistosoma japonicum , has an effect on liver fibrosis in vitro. Recombinant SJYB1 (rSJYB1) protein was expressed in a bacterial system and purified by Ni‐NTA His·Bind Resin. A human hepatic stellate cell line, the LX‐2 cell line, was cultured and treated with rSJYB1. The role of rSJYB1 on LX‐2 cells was then analysed by Western blot and luciferase assay. We succeeded in expressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…However, rSjP40 could not affect the promoter activities in cells transfected with these truncated plasmids (Figure 2B). Compared the sequences of pGL3-COL1A1 and pGL3-COL1A1a (Chen et al, 2019a), we confirmed that rSjP40 down-regulated the promoter activity of COL1A1 at the core region of -1,722/-1,592. Ets-1 May Bind to COL1A1 Promoter at the Region of -1,679/-1,673…”
Section: Results Rsjp40 Down-regulated the Activity Of Col1a1 Promoter In Lx-2 Cellssupporting
confidence: 55%
See 3 more Smart Citations
“…However, rSjP40 could not affect the promoter activities in cells transfected with these truncated plasmids (Figure 2B). Compared the sequences of pGL3-COL1A1 and pGL3-COL1A1a (Chen et al, 2019a), we confirmed that rSjP40 down-regulated the promoter activity of COL1A1 at the core region of -1,722/-1,592. Ets-1 May Bind to COL1A1 Promoter at the Region of -1,679/-1,673…”
Section: Results Rsjp40 Down-regulated the Activity Of Col1a1 Promoter In Lx-2 Cellssupporting
confidence: 55%
“…We used bioinformatics to analyze COL1A1 promoter sequences and predict possible binding sites for common transcription factors. Truncated mutation of transcription factor binding site was carried out and five luciferase reporter gene plasmids were constructed for experimental study ( Chen et al, 2019a ): pGL3-COL1A1a (-1,592/+21), pGL3-COL1A1b (-1,167/+21), pGL3-COL1A1c (-443/+21), pGL3-COL1A1d (-239/+21), pGL3-COL1A1e (-215/+21) ( Figure 2A ). Then the plasmids containing the truncated sequences of COL1A1 promoter ( Chen et al, 2019a ) were transfected into LX-2 cells, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Activated HSCs produce endothelin-1 to promote fibrogenesis[3]. A homologous protein of YB1 (a negative mediator for liver fibrosis) mediated anti-fibrotic activity by suppressing the expression of collagen type I in HSCs[4]. Moreover, Wnt signaling can also enhance HSC activation and promote liver fibrosis[5].…”
Section: Cells Involved In Liver Fibrosismentioning
confidence: 99%